THEMATIC LEARNING STRATEGIES IN AQIDAH AKHLAK LESSONS AT IBTIDAIYYAH MADRASAH SCHOOL - Diana; Rohani (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The thematic approach in the teaching and learning process is no exception to the subjects of moral aqidah in madrasas. Thematic learning models in madrasas can be said to use various models. The application of thematic learning can provide connectivity between one subject and another in order to improve and improve the quality of student learning. The application of thematic learning will help students build the meaning of new and stronger concepts and principles. The focus of attention in thematic learning lies in the process that students take when trying to understand the content of learning in line with the forms of skills that must be developed. For this reason, it is deemed necessary for all teachers to understand learning strategies and methods so that they are expected to be able to make the learning process more effective.